2022
DOI: 10.3390/plants11050702
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Genetic Diversity and Combining Ability for Some Physiological and Agronomic Traits in Rice under Well-Watered and Water-Deficit Conditions

Abstract: Water deficit is a pivotal abiotic stress that detrimentally constrains rice growth and production. Thereupon, the development of high-yielding and drought-tolerant rice genotypes is imperative in order to sustain rice production and ensure global food security. The present study aimed to evaluate diverse exotic and local parental rice genotypes and their corresponding cross combinations under water-deficit versus well-watered conditions, determining general and specific combining ability effects, heterosis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 83 publications
6
7
0
Order By: Relevance
“…The ANOVA for 12 traits in 8 × 8 half diallel set (Table 1) showed highly significant mean square estimates were recorded for genotypes, parents, crosses and the interaction among them for all root characteristics, yield and yield components under water deficit and normal conditions, except root/shoot ratio and 1000-grain weight under both conditions and leaf rolling under normal conditions which were insignificant. These results agree with those obtained by Saleem et al (2010), El-Hity et al, (2016, Daher (2018) and Sakran et al (2022). Results also revealed that variances due to the general combining ability (GCA) and the specific combining ability (SCA) were significant for all the studied traits, indicating the important of both additive and nonadditive gene action in the inheritance of all traits except root /shoot ratio and 1000-grain weight under both conditions and leaf rolling for (SCA) and (GCA) under both conditions and normal conditions, respectively.…”
Section: Analysis Of Variancesupporting
confidence: 93%
“…The ANOVA for 12 traits in 8 × 8 half diallel set (Table 1) showed highly significant mean square estimates were recorded for genotypes, parents, crosses and the interaction among them for all root characteristics, yield and yield components under water deficit and normal conditions, except root/shoot ratio and 1000-grain weight under both conditions and leaf rolling under normal conditions which were insignificant. These results agree with those obtained by Saleem et al (2010), El-Hity et al, (2016, Daher (2018) and Sakran et al (2022). Results also revealed that variances due to the general combining ability (GCA) and the specific combining ability (SCA) were significant for all the studied traits, indicating the important of both additive and nonadditive gene action in the inheritance of all traits except root /shoot ratio and 1000-grain weight under both conditions and leaf rolling for (SCA) and (GCA) under both conditions and normal conditions, respectively.…”
Section: Analysis Of Variancesupporting
confidence: 93%
“…These findings were supported by several studies ( Ahmadikhah, 2018 ; Hossain et al, 2021 ; Kamara et al, 2017 ; Tiwari et al, 2019 ), wherein it has also been suggested that these aforementioned crosses could be used to explore the heterotic effects in hybrid rice breeding programs with water deficit conditions ( Concepcion et al, 2015 ; Guimarães, Stone & Silva, 2016 ; Hassan, 2017 ; Hastini et al, 2021 ; Potkile et al, 2018 ). Furthermore, significant heterosis percentages were recorded for these traits in studied crosses, which was corroborated by previous studies ( Gaballah et al, 2021 ; Ouyang, Li & Zhang, 2022 ; Sakran et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…This juncture leads to the conclusion that these traits can be improved through conventional breeding methods and selection can be effective mostly in later generations, similar results were found by Abebe, Alamerew & Tulu (2019) and Farooq et al (2019) . High estimates of GS % expressed as mean percentages were found in all the studied traits in both crosses under both conditions, which were corroborated by the previous study ( Sakran et al, 2022 ). In addition, most of the studied traits had high estimates for h 2 b and therefore high GS, suggested that those traits are either simply inherited or governed by a few major genes, or that additive gene effects played important roles in the inheritance of these traits ( Ouyang, Li & Zhang, 2022 ).…”
Section: Discussionsupporting
confidence: 90%
“…Water deficit reduces nutrients uptake, leaf water content, and photosynthesis, which deleteriously reflect on plant growth and productivity [ 20 , 21 , 22 ]. Furthermore, drought stress induces oxidative stress by raising the production of reactive oxygen species (ROS) [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%